Specific detection of Pacific oyster (Crassostrea gigas) larvae in plankton samples using nested polymerase chain reaction - Patil, JR; Gunasekera, B; Deagle, B; Bax, NJ (2005)
Management of sustainable Pacific oyster fisheries would be assisted by an early, rapid, and accurate means of detecting their planktonic larvae. Reported here is an approach, based on polymerase chain reaction (PCR), for the detection of Pacific oyster larvae in plankton samples. Species-specific primers were designed by comparing partial mitochondrial cytochrome oxidase subunit I (COI) sequences from Crassostrea gigas, with other members of the family Ostreidae including those of Crassostrea angulata. Assay specificity was empirically validated through screening DNA samples obtained from several species of oysters. The assay was specific as only C. gigas samples returned PCR-positive results. A nested PCR approach could consistently detect 5 or more D-hinge-stage larvae spiked into a background of about 146 mg of plankton. The assay does not require prior sorting of larvae. We conclude that the assay could be used to screen environmental and ballast water samples, although further specificity testing against local bivalve species is recommended in new locations.